2022
DOI: 10.1186/s12960-022-00777-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors influencing technical efficiency of public district hospitals in KwaZulu-Natal province, South Africa

Abstract: Background District hospitals are crucial in supporting primary health care and serve as a gateway to more specialist care through a referral system. Majority of South Africans access health care services through the public sector district health system. Given the enormous task assigned to the public district hospital within the country, this study examined factors influencing their technical efficiency. Method Data were collected for 38 public dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Technical Efficiency (TE), θ CCR = Pure Technical Efficiency (PTE), θ BCC x Scale Efficiency The Fig 2 illustrates geometrically the concepts of efficiency measurement in DEA Twenty nine percent (26 of 89, 29.21%) of the included studies measured the (overall) Technical Efficiency (TE) [77102] and 26.97% (24 of 89) [75,76,103124] used TE, PTE and SE in their evaluation. While the rest of the studies evaluated their efficiency by the combination of TE and PTE and some not stated clearly the type of efficiency measured (for details see Appendix C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Technical Efficiency (TE), θ CCR = Pure Technical Efficiency (PTE), θ BCC x Scale Efficiency The Fig 2 illustrates geometrically the concepts of efficiency measurement in DEA Twenty nine percent (26 of 89, 29.21%) of the included studies measured the (overall) Technical Efficiency (TE) [77102] and 26.97% (24 of 89) [75,76,103124] used TE, PTE and SE in their evaluation. While the rest of the studies evaluated their efficiency by the combination of TE and PTE and some not stated clearly the type of efficiency measured (for details see Appendix C).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, either output expansion or input decrease is the primary evaluation goal. More than half of the studies (55.06%, 49 of 89) [4648,5054,58,60,6469,7173,7577,80,9194,96,98,99,103107,109111,113–116,118,121,124,127,128,130,135] applied input-orientated DEA models. The researchers indicated that the choice of input orientation was made to be in line with the fact that the majority of healthcare units aim to minimize inputs given a goal level of output.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations